الإنسان القرآني: دراسة مقارنة بين خصائص الإنسان وصورته في الاجتهاد الإسلامي والرؤية الغربية - عبد القادر عبد العالي (International Institute of Islamic Thought, 2019)
يتناول البحث موضوع الإنسان في القرآن الكريم؛ بُغْية تحسين فهمنا للوحي القرآني وتحيينه، عن طريق دراسة نصوص الوحي فكرياً ومنهجياً. فالدراسة الفكرية تستكشف مضامين القرآن الكريم عن الإنسان، بالاستعانة بتحليل الخطاب، وقراءة آي القرآن الحكيم بتدبُّرٍ مُنتظَم يقوم على التلقّي، والإفادة من شبكة المفاهيم الـمُتعلِّقة بالإنسان التي أنتجتها العلوم الإنسانية المعاصرة، والعلوم الشرعية الإسلامية. أما الدراسة المنهجية المستندة إلى المقارنة وتحليل المضمون، فتفيد في المقارنة بين تحليل النص القرآني في اجتهادات الـمُفكِّرين المسلمين، وتصوُّرات الفكر الفلسفي المعاصر. ويرى الباحث أنَّ تصوُّر الإنسان في القرآن الكريم يُمثِّل مشروعاً بحثياً قابلاً للإثراء والاجتهاد المفتوح على المنظورات المعيارية والواقعية والغيبية المنضبطة بالقراءة القرآنية، للكشف عن طبيعة الإنسان ومهمته ومكانته في الوجود، ويُسهِم في بناء مفهومنا عن إنسان القرآن. This paper deals with the topic of Man in the Holy Quran in order to improve and revive our understanding of the Quranic revelation, in content and methodology. Through the study of the content, using discourse analysis, systematic contemplation and making use of network of concepts in contemporary human sciences and Shariah sciences, we would discover how the Holy Quran presents Man. Through the methodological study by using comparative methods and content analysis, we would compare the analysis of Quranic text as perceived by Muslim scholars, with contemporary philosophical thought. The researcher believes that concept of human in the Holy Quran  is considered a research project capable of enrichment and open to diligent efforts of normative, realistic perspectives guided by the Quranic concept of the human nature, position and mission in the world. This would enhance our understanding of Man and contribute to building our concept of Homo-Quranicus.